The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1590/s1415-47572005000400015
|View full text |Cite
|
Sign up to set email alerts
|

Genes encoding enzymes of the lignin biosynthesis pathway in Eucalyptus

Abstract: Eucalyptus ESTs libraries were screened for genes involved in lignin biosynthesis. This search was performed under the perspective of recent revisions on the monolignols biosynthetic pathway. Eucalyptus orthologues of all genes of the phenylpropanoid pathway leading to lignin biosynthesis reported in other plant species were identified. A library made with mRNAs extracted from wood was enriched for genes involved in lignin biosynthesis and allowed to infer the isoforms of each gene family that play a major rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 51 publications
(55 reference statements)
0
28
0
2
Order By: Relevance
“…All phenylpropanoids compounds are derived from cinnamic acid, which is formed from phenylalanine by the activity of PAL. These phenylpropanoids are accountable for disease resistance, crop development and mechanical support (Barber and Mitchell, 1997;Chen et al, 2007;Harakava, 2005) as well as insect pest damages (War et al, 2012). PAL activity may be regulated by feedback inhibition by the pathway product, cinnamic acid, which may modify the expression of the PAL gene (Christensen et al, 2001;Del Rio et al, 2004).…”
Section: Phenylalanine Ammonia Lyase (Pal)mentioning
confidence: 99%
“…All phenylpropanoids compounds are derived from cinnamic acid, which is formed from phenylalanine by the activity of PAL. These phenylpropanoids are accountable for disease resistance, crop development and mechanical support (Barber and Mitchell, 1997;Chen et al, 2007;Harakava, 2005) as well as insect pest damages (War et al, 2012). PAL activity may be regulated by feedback inhibition by the pathway product, cinnamic acid, which may modify the expression of the PAL gene (Christensen et al, 2001;Del Rio et al, 2004).…”
Section: Phenylalanine Ammonia Lyase (Pal)mentioning
confidence: 99%
“…Biochemical and genetic studies further demonstrated that a key function of monolignol 4CLs is the regulation of CoA ligation fluxes to affect the total lignin content in secondary cell walls in tobacco (Nicotiana tabacum; Kajita et al, 1996), Populus spp. (Hu et al, 1999;Voelker et al, 2010), Eucalyptus grandis (Harakava, 2005), Arabidopsis (Vanholme et al, 2012), rice (Gui et al, 2011), and sorghum (Sorghum bicolor; Saballos et al, 2012). How multiple 4CL members contribute to this regulation is not clear, even though the presence of multiple members has long been known.…”
mentioning
confidence: 99%
“…Two of the predicted gene products, p-coumarate 3-hydroxylase (C3H) and CoA:shikimate/ quinate hydroxycinnamoyltransferase (HCT) had not been described previously in any Eucalyptus species. However, genes encoding trans-cinnamate 4-hydroxylase (C4H), ferulate 5-hydroxylase (F5H) and 4-coumarate: CoA ligase (4CL) had been described in other Eucalyptus species but not in E. globulus (Harakava, 2004). The remainder of the genes found had been previously described for E. globulus and published in GenBank, including phenylalanine ammonia lyase (PAL), cinnamoyl CoA reductase (CCR), cinnamyl alcohol dehydrogenase (CAD), caffeic acid O-methyltransferase (COMT) and caffeoyl-CoA 3-O-methyltransferase (CCoAOMT) ( Figure 2) (Supplementary data 2).…”
Section: Genes Predicted To Be Involved In Wood Formationmentioning
confidence: 99%